Investigating heritage sites through the lens of social media - Mahmoudi Farahani, Leila; Motamed, Bahareh; Ghadirinia, Maedeh (Journal of Architecture and Urbanism, 2018)
Today, our understanding and experience of heritage sites have been reframed by the advent of social media and the ubiquitous use of smartphones that offer more participatory ways of interacting with heritage. The lifespan of a heritage site is highly concerned with how it is understood and experienced by visitors. This study aims to investigate a heritage site and its participatory culture through the lens of social media and how a certain heritage site could be understood by these online networks. The historic city of Shiraz packed with several monumental buildings and heritage sites has been chosen as the case study of this research. Three social media platforms of Flickr, 500px and Instagram were investigated during 2015 and their photos of Shiraz were downloaded for analysis. The analysis of more than 186 images from these websites has provided an opportunity to investigate how the historical district of Shiraz is remembered in the eyes of social media users. Based on the initial photo audits, Nasir-al-Molk Mosque with more than 74 published images was the most published building and therefore was selected for an in-depth photo survey analysis. The Nasir-al-Molk Mosque images were studied regarding the physical and spiritual qualities of its building and how they contribute to its popularity among social media photographers.